The Linkage of Social Networks and Norms with the Sustainability of the Practice of “Marosok” - Qamara, Cori; Alianta, Aditya Alqamal; Hamdi, Hamdi; Widiarta, I.P.G Didik; Aprylasari, Dede (FEB Universitas Mulawarman, 2025)
In West Sumatra,